Local Government Administration in Nigeria: A Platform for Participatory Governance in Rural Decentralization - Olaoye Olumuyiwa Joseph; Joshua Kayode Okunade (Polit Journal Scientific Journal of Politics, 2026)
The evolution of governance is inherently linked to the establishment of family and societal structures, which have led to a complex and organized local government system considered fundamental for any society (Jamo, 2006). In Nigeria, local government represents the third tier of governance, established by the Constitution of the Federal Republic of Nigeria primarily to facilitate rural development effectively. Its proximity to rural communities positions local governments as crucial administrative entities responsible for providing social and economic services, thereby enhancing living standards and enabling conditions for development (Ojinnaka & Ohazurike, 2024). The 1999 Constitution outlines that local governments exist to bridge the service delivery gap that federal and state governments cannot fill due to their geographical remoteness from local communities. This constitutional provision emphasizes the imperative to decentralize governance, bringing it closer to citizens to foster socio-economic and political advancement in rural areas (Ojinnaka, 2018). Moreover, Section 7 (1) mandates that local governments in Nigeria be democratically elected, reinforcing their role in governance despite past reforms, including the significant 1976 restructuring aimed at enhancing local government's capacities. However, the performance of local governments in Nigeria concerning their statutory obligations has been suboptimal. The rationale for local government creation globally highlights its essential function in promoting grassroots development. Furthermore, local governance plays a vital role in establishing a sense of belonging among community members, fostering national unity, and nurturing democratic awareness—particularly important within Nigeria's heterogeneous socio-political landscape characterized by ethnic, linguistic, and religious diversity. Scholarly definitions of local government emphasize the concept as a means of transferring political authority to localities, allowing residents to engage directly in addressing their community's needs.